A experiência de narrar o desconhecido: o engenho da ficção no romance “O irmão alemão”, de Chico Buarque - Chaves, Anderson Trindade (2020)
The present work aims to present a critical reading of novel O irmão alemão by Chico Buarque, in order to analyze it as a narrative composition that articulates an ambiguous literaty representation between its mimetic referents of a historical-social reality and their fictionalization indexes of that same reality from the narrador-protagonist‘s account of the search for his supposed Jewish brother who disappeared in the context of a Nazi Germany. In this sense, we base our approach not only on the treoretical formulations that deal with the socalled ―narratives of the self‖, but above all to those that explain the tradition of the novel/romance genre from its condition of ambiguity regarding historical-social world from which it comes and participates in and, above all, by questioning it and reinventing it through it fictional processes. From this, we move on to the proper analysis of the novel in question, in order to highlight the changing modulation in the structure of its meanings, which prevents the work from being appreciated through a single model of literary writing. It is precisely the strained relationship between its strata of meaning that allows levels of interpretation and reading for the decoding of the novel. Thus, we understand that the universe of the narrated facts is the most important in the discursive articulation of the narrative. On the contrary, the experience oh interpretation, sensitive perception and imagination of historical reality from the perspective of a narrator-protagonist is what plurify the semantic and fictional expression of the narrative present in O irmão alemão, by Chico Buarque.